Economic growth: productivity, thrift and capital accumulation - Villalobos Céspedes, Daniel (2020)
The aim of this research is to study the relationship between thrifts, capital accumulation, and economic growth, as suggested by Swan in 1956. It provides a model which measures resource contribution, productivity, and share on economic growth and explains how it could occur in an economy. New formulas emerge as powerful tools in building a rigorous new method of attack to support the analysis and explanation of this subject, which was evaluated by the case of Costa Rica during the period 2010 – 2017. The theoretical and empirical findings of the analysis of capital and labor productivity, contribution, and share on economic growth support Swan’s suggestion.